Microembolus Detection by Transcranial Doppler Sonography: Review of the Literature - Vlasta Vuković-Cvetković (Stroke Research and Treatment)
Transcranial Doppler can detect microembolic signals which are characterized by unidirectional high intensity increase, short duration, random occurrence, and a “whistling” sound. Microembolic signals have been detected in a number of clinical settings: carotid artery stenosis, aortic arch plaques, atrial fibrillation, myocardial infarction, prosthetic heart valves, patent foramen ovale, valvular stenosis, during invasive procedures (angiography, percutaneous transluminal angioplasty), surgery (carotid, cardiopulmonary bypass, orthopedic), and in certain systemic diseases. Microembolic signals are frequent in large artery disease, less commonly detected in cardioembolic stroke, and infrequent in lacunar stroke. This article provides an overview about the current state of technical and clinical aspects of microembolus detection.